Evaluating the Impact of Electric Vehicles on Emission Reduction in Schools: A Case Study at SMP Darul Hikam Bandung - Padmadewi, Ayu Laksmi; Ramadhani, Umar Hanif; Edypoerwa, Mugni Labib; Trisno, Bambang (International Journal of Educational Management and Innovation, 2025)
Reducing greenhouse gas emissions and air pollution is a critical challenge in mitigating climate change and improving air quality, particularly in densely populated urban areas. This study analyzes and optimizes emission reductions from motor vehicles at SMP Darul Hikam Bandung, with 38 vehicles as the sample. Three vehicles are evaluated: gasoline-powered motorcycles, electric motorcycles charged from the public electricity grid (PLN), and electric motorcycles charged using renewable energy sources. The goal is to determine which vehicle type generates the lowest pollution by considering direct emissions from fuel combustion and indirect emissions associated with electricity generation. The methodology employed is Life Cycle Analysis (LCA), which measures total emissions from each vehicle type, production to operation, and end-of-life battery management. Gasoline motorcycles are assessed based on emissions from fuel combustion, while electric motorcycles are analyzed according to their charging source. Electric motorcycles charged from the PLN grid are evaluated for emissions related to electricity generation. In contrast, those charged from renewable energy sources consider the environmental impact of battery production and energy storage at charging stations. The results of this study are expected to provide more precise insights into the most environmentally friendly vehicle options and offer policy recommendations for selecting vehicles that minimize emissions in school and urban environments.